2023
DOI: 10.1002/slct.202203935
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating Superhydrophobic Protective Films with Enhanced Self‐Cleaning and Anti‐Corrosion Properties through Multiple Anodic Oxidations on Aluminum Alloys

Abstract: The development of aluminum (Al) alloys with superb anticorrosion and self-cleaning properties for prolonging the working life and reducing maintenance cost is a hot topic of concern. Since anodic oxidation has been proven to be an effective technique to prepare micro or nanostructures on Al alloys surface, this study proposes a novel and scalable multiple anodic oxidations method with gradient current densities for fabricating hierarchical micro-nanostructure film with appropriate roughness on Al alloys, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…To obtain essential components in superhydrophobicity, namely, roughness and low adhesion to water, various surface modification technologies and methods have been developed, such as electrodeposition, electrospinning, spraying, chemical vapor deposition, and immersion coating. [24][25][26][27][28] Recently, it has been reported that Qi et al proposed an advanced method, they prepared micro/nanostructures and surface layers enriched with organic groups through nonsolvent-induced phase separation method for preparing superhydrophobic surfaces. [29] Wang et al compared different pretreatments for electrodepositing nickel-phosphorus coatings on the Al alloy surface and proposed an electrodeposition model using anodic oxidation pretreatment.…”
mentioning
confidence: 99%
“…To obtain essential components in superhydrophobicity, namely, roughness and low adhesion to water, various surface modification technologies and methods have been developed, such as electrodeposition, electrospinning, spraying, chemical vapor deposition, and immersion coating. [24][25][26][27][28] Recently, it has been reported that Qi et al proposed an advanced method, they prepared micro/nanostructures and surface layers enriched with organic groups through nonsolvent-induced phase separation method for preparing superhydrophobic surfaces. [29] Wang et al compared different pretreatments for electrodepositing nickel-phosphorus coatings on the Al alloy surface and proposed an electrodeposition model using anodic oxidation pretreatment.…”
mentioning
confidence: 99%